Transdisciplinary solutions to methodological and ethical problems in performing arts psychology - Pil Hansen (Frontiers in Psychology, 2024)
In the first part of this article, I argue that transdisciplinary research can help address both the WEIRD problem of homogenous samples and the categorical problem of overgeneralized practice conceptions in performing arts psychology. Like other areas of performance science, performing arts psychology engages with practices and practice-based knowledge that are studied differently by subject-specific disciplines. I propose a transdisciplinary research model that facilitates greater overlap and transfer between the scientific, subject-specific, and practice-based forms of research and knowledge that surround a practice. The potential benefits of such a model are more inclusive samples, diversified methods, grounded research questions, and widely applicable results. The problems mentioned above are also ethical. Psychological definitions of performance that derive from overgeneralized conceptions and overreliance on homogenous samples are transferred to diverse peoples, practices, and contexts as general knowledge. This fails to apply principles of equity and relational ethics, which in turn reveals some limitations of established ethics procedures. In the second section of this article, I therefore revisit my argument for transdisciplinary research, now with a focus on the triad of research ethics that is brought into a transdisciplinary project through the different priorities of scientific, subject-specific, and practice-based research domains; namely, procedural ethics, relational ethics, and principles of equity. Transdisciplinary researchers are not only negotiating across methodological paradigms that determine research validity, they are also negotiating across ethical values. Combining the two sections of the article, I argue that the challenge of negotiation can be flipped into a solution to the WEIRD and practice conception problems in performing arts psychology. I argue that whereas critical calls for radical departures were needed to identify these problems, solutions are available in bridges between different ethical and methodological approaches.